Pengaruh Penempatan Kerja dan Beban Kerja terhadap Prestasi Kerja : ( Studi Pada Karyawan Bank BJB Cabang Majalengka ) - Haris Fauzi (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
ABSTRACT This study aims to determine how the effect of work placement and workload on study achievement on employees of Bank BJB Majalengka branch partially. This research is a survey research using a descriptive and verification approach. The population in this study were all employees of Bank BJB Majalengka Branch with a sample of 96 respondents. The sampling technique used is Nonprobability Sampling with Saturated Sampling. The data collection technique in this study was a questionnaire using a Likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination, partial hypothesis testing. The results of hypothesis testing indicate that work placement has a significant effect on job performance. That is, the better the work placement is carried out, the higher the work performance of the employees, the workload has a significant effect on work performance. That is, the more appropriate the workload, the higher the employee's work performance